Glycosidase‐Catalyzed Synthesis of Glycosyl Esters and Phenolic Glycosides of Aromatic Acids. Issue 11 (6th May 2019) - Bassanini, Ivan; Kapešová, Jana; Petrásková, Lucie; Pelantová, Helena; Markošová, Kristína; Rebroš, Martin; Valentová, Kateřina; Kotik, Michael; Káňová, Kristýna; Bojarová, Pavla; Cvačka, Josef; Turková, Lucie; et al.
Abstract: Phenolic glycosides occur naturally in many plants and as such are often present in the human diet. Their isolation from natural sources is usually laborious due to their presence in complex matrices. Their chemical and enzymatic syntheses have been found complex, time‐consuming, and costly, yielding only small amounts of glycosylated products. In quest of a convenient biocatalytic route to structurally complex phenolic glycosides, we discovered that the rutinosidase from Aspergillus niger not only efficiently converts hydroxylated aromatic acids ( e. g . coumaric and ferulic acids) into the respective phenolic rutinosides, but surprisingly also catalyzes the formation of the respective glycosyl esters. We report here the results of a systematic study presenting the unique synthesis of naturally occurring glycosyl esters and phenolic glycosides accomplished by glycosidase catalysis. A panel of aromatic acids was tested as glycosyl acceptors and the crucial structural features required for the formation of glycosyl esters were identified. In the light of the present structure‐activity relationship study, a plausible reaction mechanism was proposed. All the products were fully structurally characterized by NMR and MS. Abstract :